The Hesistency of Public Toward COVID-19 Vaccine Booster in Indonesia - Palupi Triwahyuni; Charissa Angie Victorine Simbolon (Malahayati Nursing Journal, 2023)
ABSTRACT Until now, the transmission of the Corona virus disease (COVID-19) is still there. According to the magazine Folkative daily in June 2022 that Omicron BA.4 and BA.5 subvariants were identified enter Indonesia. More than two years into the coronnavirus pandemic, doctors are seeing other viruses, like the flu, act in unusual ways. COVID is making flu and other common viruses act in unfamiliar ways (The Washington Post, June, 2022). The Ministry of Communication and Information of the Republic of Indonesia (KOMINFO, 2022) continuously calls for all people in Indonesia to get a complete dose of 1,2 and booster vaccines. This is to increase immunity so that COVID-19 does not have a severe impact. The booster vaccine can be obtained at Public Health Centers or vaccine centers. This study uses qualitative methods with the phenomenology approach. There are 12 informants on this research which are adults who are willing to become research informants. The data are gathered using a survey with purposive sampling and in-depth interviews. Coallizi's method are used to analyze the interview results. From this research can be found that the informants have knowledge of COVID-19 from pandemic to endemic, know about the type of COVID-19 vaccine, have strong reasons for refusing to give a COVID-19 vaccine booster, believe that a COVID-19 vaccine booster is unnecessary If done, the body already has immunity without having to receive a COVID-19 vaccine booster. This research can be an input to find out more about the public's views on the administration of the COVID-19 Keyword: hesistency, COVID-19 vaccine booster